Heterologous expression of cellulase gene from bacillus Amyloliquefacians UMAS 1002 in Escherichia Coli BLl21 (DE3) - Komathi, Balasupramaniam (Universiti Malaysia Sarawak, UNIMAS, 2010)
Cloning and expression of cellulase gene from B. amyloliquefaciens in E. coli BL21 (DE3) was attempted to optimize the activity of recombinant cellulase. PCR amplification of cellulase gene from Top10 cell was not successful although different approaches were carried out. Alternative method was taken as time become limiting factor for further works. The pET100 with subcloned cellulase gene was used for expression studies and the work started with extraction of pET100 from Top10 cell and transformation into expression host, E. coli BL21 (DE3). Screening of cellulolytic organisms carried by Congo red assay revealed that recombinant CMCase activity on the LB media is higher compared to minimal media. This is based on measurement of diameters of the clear zone produced on CMC plates. Besides the clearing zones on plates, enzymatic and Bradford assay were used to determine the cellulase activity of the selected bacterial isolate in liquid medium. Different parameters including temperature and pH were analyzed to identify cellulase maximal activity. Recombinant cellulase from E.coli BL21 (DE3) was shown to have higher activity at temperature 37°C and pH 7. SDS-PAGE analysis showed the presence of two intense bands with estimated molecular weight of about 42kDa and 40kDa. It was suggested that partial degradation of the enzyme took place due to a proteolytic cleavage and this cleavage from the C-terminal ends of the gene could have given rise to the smaller active bands.